Pengaruh Pemberian Kopi Robusta (Coffea canephora) terhadap Penurunan Kadar Glukosa Darah pada Tikus Rattus norvegicus dengan Kondisi Diabetes Melitus - Sofyanita, Eko Naning; Maulana, Mochamad Rizal; Auliya, Qurrotu A'yuni; Setyowatiningsih, Lilik; Swastyaputri, Adita Puspitasari (ARTERI : Jurnal Ilmu Kesehatan, 2024)
Diabetes Mellitus (DM) leads to an increase in Reactive Oxygen Species (ROS), which disrupts the function of pancreatic β-cells. The dependency on medications often occurs, hence there is a need for natural remedies with antihyperglycemic properties, such as coffee. Coffee contains high levels of antioxidants like chlorogenic acid, flavonoids, and caffeine, which are exogenous antioxidants that can activate NRF-2 and increase the activity of the enzyme Superoxide Dismutase (SOD), thus acting as an antihyperglycemic agent. This study aims to determine the effect of robusta coffee on blood glucose levels in rats with DM conditions. This experimental study used a Randomized Control Pretest-Posttest Group Design. The sample in this study included 24 male Rattus norvegicus rats, aged 3 months, with a body weight of 230-250 grams, divided into 4 groups randomly after a one-week acclimation period. The DM condition was induced by administering streptozotocin at 40 mg/KgBW, followed by a pretest blood glucose level examination after 3 days of streptozotocin induction. The diabetic rats were then given robusta coffee once a day for a period of 14 days. On the 15th day, a posttest blood glucose level examination was conducted. The results showed that the control group (KN) had no significant difference (p=0.530), while the treatment groups KP (p=0.003), KK1 (p=0.013), and KK2 (p=0.000) showed significant differences (p<0.05). The conclusion of this study is that the administration of robusta coffee (Coffea canephora) can reduce blood glucose levels in rats with diabetes mellitus.